New Technological Revolution and Energy Requirements - Sergey Filippov (Foresight and STI Governance)
The new technological revolution is radically changing the shape and development conditions of the world energy industry. The increase in demand for energy, alongside with changes in its structure, require the development of breakthrough technologies and the supply of new energy resources, which is associated with significant costs. To optimize them, a timely anticipation of the expected socio-economic changes and future energy requirements is needed.